The Effects of Immersive Virtual Reality in Reducing Public Stigma of Mental Illness in the University Population of Hong Kong: Randomized Controlled Trial - Yuen, Anna S Y (J Med Internet Res, 2021)
BACKGROUND: Public stigma in mental health often brings various adverse effects on people with mental illness. Researchers have been developing different interventions in combating public stigma. OBJECTIVE: This study investigates the effects of immersive virtual reality (IVR) in reducing the public stigma of mental illness using a single-blinded randomized control trial. METHODS: A pre-post experimental design with a 1-week follow-up was conducted. Participants (N=206) were recruited through the mass mail system of The Chinese University of Hong Kong and randomized into 3 conditions: immersive animation, text, and control. In the immersive animation condition (n=72), participants experienced the simulation of daily life and the stigma experienced as an animated story protagonist with mixed anxiety and depressive disorder with IVR. In the text condition (n=65), participants experienced an identical story to the immersive animation condition with first-person audio narration using the same virtual reality headset. In the control condition (n=69), participants watched a video about planets with IVR. All participants received interventions with a researcher-assisted Oculus Go virtual reality headset. Participants’ public stigma was measured through self-administered online questionnaires and compared across conditions and at different time points using repeated measures analysis of variance. Simple and sequential mediation analyses on the relationship of condition (immersive animation vs text) and follow-up public stigma with possible mediators, including sense of embodiment and story transportation, were conducted using PROCESS. RESULTS: Public stigma did not differ significantly across conditions at pre-experiment (P>.99). In the immersive animation and text conditions, public stigma was significantly reduced at postexperiment and at the 1-week follow-up compared to pre-experiment (all with P<.001). Public stigma in the control condition at postexperiment and follow-up remained unchanged compared with pre-experiment (P=.69). Immersive animation had significantly lower public stigma than the control at postexperiment (P=.003) and follow-up (P=.02). Text also had lower public stigma than the control at postexperiment (P=.007) and follow-up (P=.03). However, immersive animation did not significantly differ from text in public stigma at postexperiment and follow-up (both P>.99). In simple mediation models, both sense of embodiment (95% CI –0.22 to 0.46) and story transportation (95% CI –0.18 to 0.00) were not significant mediators. In the sequential mediation model, both sense of embodiment and story transportation were significant sequential mediators. Sense of embodiment was positively associated with story transportation (P<.001), while story transportation was negatively associated with public stigma (P<.001). The indirect effect of the sequential mediation model was significant (95% CI –0.38 to –0.11). CONCLUSIONS: This study provides novel findings and a rigorous comparison in understanding the effects of IVR on public stigma. The findings showed that IVR and text with audio narration performed similarly and significantly in stigma reduction. Sense of embodiment and story transportation were found to be sequentially associated with public stigma reduction. TRIAL REGISTRATION: Centre for Clinical Research and Biostatistics Clinical Trial Registry CUHK_Ccrb00638; https://www2.ccrb.cuhk.edu.hk/registry/public/632